Description of Blood Sugar Levels of Male Wistar Rats after Administration of Ethanol Extract of Rambusa Leaves (Passiflora Foetida Linn.) from Central Kalimantan - Evi Mulyani; Noor Alris Ferdiansyah; Halida Suryadini; Husna Fauzia (GLOBAL HEALTH SCIENCE GROUP, 2025)
Rambusa (Passiflora foetida Linn.) is a type of plant that is often found creeping on other plants. Usually found in watery areas such as swamps and rivers. The rambusa plant contains chemical compounds which are useful sources and can be developed as medicine. Several previous studies explained that Rambusa (Passiflora foetida Linn.) which grows in several areas shows antidiabetic properties. The aim of this study was to determine the blood sugar levels of male Wistar rats after administration of ethanol extract of rambusa leaves (Passiflora foetida Linn.) from Central Kalimantan. This research was carried out using an experimental or experimental method (experiment research) in the laboratory which was carried out with a series of experiments using the GCU Check strip. The results of this study show that ethanol extract of rambusa leaves from Central Kalimantan can reduce blood sugar levels of male Wistar rats at doses of 1.5 mg/Kgbb and 2 mg/Kgbb.